Instrumentos financeiros derivativos: gestão de risco em empresas brasileiras não financeiras e os efeitos das alterações advindas do CPC 14/2008 e instrução CVM N°475/2008 - Nirlene Aparecida Carneiro Fernandes (2011)
The derivatives market has been gaining importance in the global economic context, which requires properly accounting procedures that demonstrate the risks and benefits involved in V such transactions. It is noteworthy that the role of these instruments as a means of management and risk control is critical in that it allows the transfer of risks between different actors. Given the importance that the derivative transactions may have on the company's financial health and the recent regulation of these operations, which requires greater transparency in relation to managed risks of derivatives, it is questionable what the effects of the recent Brazilian regulations on the management of derivatives risk of nonfinancial Brazilian companies. Thus, the overall objective of the study was to examine the effects of changes in the recognition, measurement and disclosure of derivative financial instruments, coming from the CPC 14/08 and CVM Instruction No. 475/08, on the risk management of Brazilian companies non-financial listed on the BOVESPA, in the aftermath of recent regulations, the years ended 2008 and 2009, To this end, we carried out a descriptive- explanatory, with a quantitative approach, using techniques of data collection and content analysis documentary research. The documents examined were the financial statements of non-financial companies listed on the BOVESPA on May 25, 2010, and the final sample of 42 companies and users of derivatives 42 companies nonusers of derivatives. As a result it I l was found that the classes of risk managed with derivatives in Brazil are the foreign exchange exposure, interest rate and commodity prices, in this order, the Brazilian non-financial companies use derivatives with the primary purpose of managing risks, and not for speculative purposes, and, in general, it was noted that the recent regulation of derivatives had no significant effect for companies classified as hedgers effective but reduced the risk exposure of companies classified as ineffective hedgers / speculators. It was concluded that the recent regulation of derivatives has shown no significant effects for companies classified as hedgers effective but has reduced the risk exposure of companies classified as ineffective hedgers / speculators